Asphalt modifier for straight asphalt

JP7641823B2Active Publication Date: 2025-03-07KAO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021087700
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-25
Publication Date
2025-03-07
Estimated Expiration
2041-05-25

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、より一層優れた耐わだち掘れ性及び表面美観を有する舗装面が形成されるアスファルト混合物を得るためのストレートアスファルト用アスファルト改質剤、アスファルト混合物及びその製造方法、並びに道路舗装方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641823000001
    Figure 0007641823000001
  • Figure 0007641823000002
    Figure 0007641823000002
  • Figure 0007641823000003
    Figure 0007641823000003
Patent Text Reader

Abstract

To provide: an asphalt paving mixture, with which a paved surface having excellent rutting resistance and surface beauty is formed; and an asphalt modifier for straight asphalt to obtain the asphalt paving mixture.SOLUTION: Provided is an asphalt modifier for straight asphalt, comprising a polyester (A) and a polyester (B). The polyester (A) comprises a structural unit of an alcohol component (a-1) and a structural unit of a carboxylic acid component (a-2) where, of a total of 100 mol% of the components, a total content of an alcohol component and a carboxylic acid component having specific structures is 10 mol% or more. The polyester (B) comprises a structural unit derived from an alcohol component (b-1) and a structural unit derived from a carboxylic acid component (b-2) where of a total of 100 mol% of the components, a total content of an alcohol component and a carboxylic acid component having aliphatic saturated hydrocarbon skeletons is 20 mol% or more and a total content of an alcohol component and a carboxylic acid component having specific structures is less than 5 mol%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an asphalt modifier for straight asphalt, an asphalt mixture and a method for producing the same, and a road paving method. [Background technology]

[0002] Asphalt pavement, which uses asphalt mixture, is used for paving roads, parking lots, freight yards, sidewalks, etc., because it is relatively easy to lay and the time from the start of paving work to the start of traffic is short. Asphalt pavement has a road surface formed from an asphalt mixture in which aggregate is bound with asphalt, the paved road has good hardness and durability. However, asphalt pavement surfaces deteriorate over time and require repair, which increases maintenance costs and has a significant impact on automobile traffic.

[0003] Patent Document 1 discloses an asphalt composition comprising asphalt, a thermoplastic elastomer, and a specific amount of a polyester, the polyester having a specific softening point and glass transition point. Patent Document 2 discloses an asphalt composition containing asphalt and a polyester-based polymer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-19325 A [Patent Document 2] Japanese Patent Application Publication No. 04-8766 Summary of the Invention [Problem to be solved by the invention]

[0005] When asphalt is modified with polyester containing a bisphenol A skeleton, rutting on the pavement surface after construction is suppressed, and a pavement surface with excellent resistance to rutting (rutting resistance) and a beautiful surface is formed. However, there is a demand for asphalt mixtures that can produce pavement surfaces with even better rutting resistance. In particular, there have been cases where rutting resistance was insufficient in specially formulated asphalt pavements such as drainage pavements and thin-layer pavements, which tend to have insufficient thermal curing. The present invention relates to an asphalt modifier for straight asphalt to obtain an asphalt mixture that forms a pavement surface having even better rut resistance and surface beauty, an asphalt mixture and a method for producing the same, and a road paving method. [Means for solving the problem]

[0006] The present invention relates to the following [1] to [5]. [1] An asphalt modifier for straight asphalt comprising a polyester (A) and a polyester (B), The polyester (A) contains a structural unit derived from an alcohol component (a1) and a structural unit derived from a carboxylic acid component (a2), and the total content of the alcohol component and the carboxylic acid component having a structure represented by the following formula (1) is 10 mol % or more relative to 100 mol % in total of the alcohol component (a1) and the carboxylic acid component (a2): The polyester (B) comprises a structural unit derived from an alcohol component (b1) and a structural unit derived from a carboxylic acid component (b2), and, in a total of 100 mol % of the alcohol component (b1) and the carboxylic acid component (b2), the total content of the alcohol component having an aliphatic saturated hydrocarbon skeleton and the carboxylic acid component is 20 mol % or more, and the total content of the alcohol component and the carboxylic acid component having a structure represented by the following formula (1) is less than 5 mol %.

[0007] [ka]

[0008] [2] An asphalt mixture comprising straight asphalt, aggregate, the polyester (A) described in [1] above, and the polyester (B) described in [1] above. [3] An asphalt mixture comprising straight asphalt, aggregate, the polyester (A) described in [1] above, and the polyester (B) described in [1] above. [4] A method for producing the asphalt mixture according to [2] or [3] above, comprising a step of mixing straight asphalt, heated aggregate, polyester (A) and polyester (B). [5] A road paving method comprising the step of applying the asphalt mixture according to [2] or [3] above to a road to form an asphalt pavement layer. Effect of the Invention

[0009] According to the present invention, it is possible to provide an asphalt modifier for straight asphalt, an asphalt mixture and a method for producing the same, and a road paving method, which are capable of obtaining an asphalt mixture that forms a pavement surface having even better rut resistance and surface aesthetics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] [Asphalt modifier for straight asphalt] The asphalt modifier for straight asphalt of the present invention comprises a polyester (A) and a polyester (B), the polyester (A) contains a structural unit derived from an alcohol component (a1) and a structural unit derived from a carboxylic acid component (a2), and the total content of the alcohol component and the carboxylic acid component having a structure represented by formula (1) is 10 mol % or more relative to 100 mol % in total of the alcohol component (a1) and the carboxylic acid component (a2), The polyester (B) contains a structural unit derived from an alcohol component (b1) and a structural unit derived from a carboxylic acid component (b2), and in a total of 100 mol % of the alcohol component (b1) and the carboxylic acid component (b2), the total content of the alcohol component having an aliphatic saturated hydrocarbon skeleton and the carboxylic acid component is 20 mol % or more, and the total content of the alcohol component and the carboxylic acid component having a structure represented by formula (1) is less than 5 mol %.

[0011] [ka]

[0012] The present inventors have discovered that by incorporating a combination of a specified polyester (A) and a specified polyester (B) into an asphalt mixture containing straight asphalt, a pavement surface having even better rut resistance and surface beauty can be formed. Although the detailed mechanism by which the effects of the present invention are obtained is unclear, part of it is thought to be as follows. Asphalt components are roughly classified into asphaltene and maltene. In the present invention, it is presumed that the polyester (A) having a specific structure effectively modifies the asphaltene to improve the hardness of the pavement, and the polyester (B) having a specific structure effectively modifies the maltene to impart adhesion to aggregates. Furthermore, since polyester (A) and polyester (B) each have a specified structure and have a structure that enhances the compatibility between the polyesters and with the other components, the respective effects are exerted synergistically, and it is believed that excellent rut resistance and high durability can be exhibited in asphalt mixtures that use straight asphalt, which tends to have low compatibility with polyesters, and therefore excellent surface aesthetics can be provided.

[0013] The definitions of various terms used in this specification are given below. The term "binder mixture" refers to a mixture containing asphalt and a thermoplastic elastomer, and is a concept that includes, for example, asphalt modified with the thermoplastic elastomer described below (hereinafter also referred to as "modified asphalt"). In the polyester, a "structural unit derived from an alcohol component" means a structure obtained by removing a hydrogen atom from a hydroxy group of an alcohol component, and a "structural unit derived from a carboxylic acid component" means a structure obtained by removing a hydroxy group from a carboxy group of a carboxylic acid component. The term "carboxylic acid component" includes not only the carboxylic acid itself, but also anhydrides that decompose during the reaction to generate an acid, and alkyl esters of carboxylic acids (for example, alkyl groups having 1 to 3 carbon atoms). When the carboxylic acid component is an alkyl ester of carboxylic acid, the number of carbon atoms of the alkyl group that is the alcohol residue of the ester is not included in the number of carbon atoms of the carboxylic acid.

[0014] <Polyester (A)> From the viewpoint of rut resistance and surface appearance of asphalt pavement, polyester (A) contains a constituent unit derived from alcohol component (a1) and a constituent unit derived from carboxylic acid component (a2), and in a total of 100 mol % of alcohol component (a1) and carboxylic acid component (a2), the total content of alcohol component and carboxylic acid component having a structure represented by formula (1) is 10 mol % or more, preferably 20 mol % or more, more preferably 25 mol % or more, even more preferably 40 mol % or more, and preferably 70 mol % or less, preferably 60 mol % or less, even more preferably 55 mol % or less. [ka]

[0015] (Structure represented by formula (1)) The structure represented by formula (1) is a 4,4'-isopropylidenediphenyl structure. In one preferred embodiment of the present invention, the structure represented by formula (1) is a structure containing a bisphenol A skeleton represented by the following formula (1').

[0016] [ka]

[0017] The structure represented by formula (1) may be present in both the alcohol component (a1) and the carboxylic acid component (a2), or in either the alcohol component (a1) or the carboxylic acid component (a2), and preferably only in the alcohol component (a1).

[0018] (Alcohol component (a1)) The alcohol component (a1) may be a diol, a trihydric or higher polyhydric alcohol, etc. The diol may be an aliphatic diol, an aromatic diol, etc. These alcohol components may be used alone or in combination of two or more. From the viewpoint of rutting resistance and surface appearance of an asphalt pavement, the alcohol component (a1) preferably contains an alkylene oxide adduct of bisphenol A, and more preferably contains an alkylene oxide adduct of bisphenol A represented by the following formula (I). [ka] [In the formula, OR 1 and R 1 O is an alkylene oxide, and R 1 is an alkylene group having 2 or 3 carbon atoms, x and y are positive numbers indicating the average number of moles of alkylene oxide added, and the sum of x and y is preferably 1 or more, more preferably 1.5 or more, and is preferably 16 or less, more preferably 8 or less, and even more preferably 4 or less.

[0019] Examples of the alkylene oxide adduct of bisphenol A represented by formula (I) include a propylene oxide adduct of bisphenol A [2,2-bis(4-hydroxyphenyl)propane] and an ethylene oxide adduct of bisphenol A. These alkylene oxide adducts of bisphenol A can be used alone or in combination of two or more kinds.

[0020] From the viewpoint of rut resistance and surface appearance of the asphalt pavement, the content of the alkylene oxide adduct of bisphenol A is preferably 20 mol % or more, more preferably 25 mol % or more, and even more preferably 30 mol % or more, based on 100 mol % of the alcohol component (a1), and is preferably 100 mol % or less.

[0021] Examples of the aliphatic diol include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,4-butenediol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 1,10-decanediol, and 1,12-dodecanediol. Examples of the polyhydric alcohol having a valence of three or more include trihydric alcohol, etc. Examples of the polyhydric alcohol having a valence of three or more include glycerin, etc.

[0022] (Carboxylic acid component (a2)) Examples of the carboxylic acid component (a2) include aliphatic dicarboxylic acid compounds, aromatic dicarboxylic acid compounds, and polyvalent carboxylic acid compounds having a valence of 3 to 6. These carboxylic acid components can be used alone or in combination of two or more.

[0023] The number of carbon atoms in the main chain of the aliphatic dicarboxylic acid is preferably 3 or more, more preferably 4 or more, and preferably 10 or less, more preferably 8 or less, from the viewpoints of rut resistance and surface appearance of the asphalt pavement. Examples of the aliphatic dicarboxylic acid compound include fumaric acid, maleic acid, oxalic acid, malonic acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, adipic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, and succinic acid substituted with an alkyl group having 1 to 20 carbon atoms or an alkenyl group having 2 to 20 carbon atoms. Examples of the substituted succinic acid include dodecylsuccinic acid, dodecenylsuccinic acid, and octenylsuccinic acid. Among the above aliphatic dicarboxylic acid compounds, adipic acid and succinic acid substituted with an alkenyl group having 2 to 20 carbon atoms are preferred.

[0024] Examples of aromatic dicarboxylic acid compounds include phthalic acid, isophthalic acid, terephthalic acid, naphthalenedicarboxylic acid, etc. Among the above aromatic dicarboxylic acid compounds, from the viewpoint of rutting resistance and surface appearance of asphalt pavement, isophthalic acid and terephthalic acid are preferred, and terephthalic acid is more preferred. The polyvalent carboxylic acid compound having a valence of 3 to 6 is preferably a trivalent carboxylic acid. Examples of the polyvalent carboxylic acid compound having a valence of 3 to 6 include trimellitic acid, 2,5,7-naphthalenetricarboxylic acid, and pyromellitic acid. When the polyvalent carboxylic acid compound is contained, from the viewpoint of the rutting resistance and surface appearance of the asphalt pavement, the alcohol component may appropriately contain a monovalent alcohol, and the carboxylic acid component may appropriately contain a monovalent carboxylic acid compound.

[0025] From the viewpoint of the rut resistance and surface appearance of the asphalt pavement, the content of the aliphatic dicarboxylic acid compound in the carboxylic acid component (a2) is preferably 1 mol % or more, more preferably 5 mol % or more, even more preferably 7 mol % or more, and is preferably 40 mol % or less, more preferably 30 mol % or more, even more preferably 25 mol % or less. From the viewpoint of rut resistance and surface appearance of the asphalt pavement, the content of the aromatic dicarboxylic acid compound is preferably 50 mol% or more, more preferably 60 mol% or more, even more preferably 75 mol%, and is 100 mol% or less, preferably 98 mol% or less, more preferably 95 mol% or less, and even more preferably 90 mol% or less, out of 100 mol% of the carboxylic acid component.

[0026] In one preferred embodiment of the present invention, the carboxylic acid component (a2) contains at least one selected from the group consisting of terephthalic acid and isophthalic acid in a total amount of at least 50 mol %, and from the viewpoint of the rutting resistance and surface appearance of the asphalt pavement, this is preferably at least 60 mol %, more preferably at least 80 mol %, and is preferably at most 100 mol %.

[0027] (Molar ratio of carboxylic acid component (a2) to alcohol component (a1)) The molar ratio of the carboxylic acid component (a2) to the alcohol component (a1) [carboxylic acid component (a2) / alcohol component (a1)] is preferably 0.6 or more, more preferably 0.7 or more, even more preferably 0.8 or more, from the viewpoint of adjusting the acid value and from the viewpoint of the rutting resistance and surface appearance of the asphalt pavement, and is preferably 1.5 or less, more preferably 1.3 or less, even more preferably 1.1 or less.

[0028] (Structural unit derived from polyethylene terephthalate) The polyester (A) may contain a structural unit derived from ethylene glycol and a structural unit derived from terephthalic acid derived from polyethylene terephthalate. The polyethylene terephthalate may contain a small amount of components such as butanediol and isophthalic acid in addition to the structural units derived from ethylene glycol and terephthalic acid. The polyethylene terephthalate is preferably recycled polyethylene terephthalate. When the polyester (A) contains structural units consisting of ethylene glycol and terephthalic acid derived from polyethylene terephthalate, the "structural units derived from the alcohol component (a1)" contain structural units derived from ethylene glycol derived from polyethylene terephthalate, and the "structural units derived from the carboxylic acid component (a2)" contain structural units derived from terephthalic acid derived from polyethylene terephthalate.

[0029] (Physical properties of polyester (A)) From the viewpoint of rut resistance and surface appearance of the asphalt pavement, the softening point of the polyester (A) is preferably 85°C or higher, more preferably 90°C or higher, even more preferably 95°C or higher, and is preferably 140°C or lower, more preferably 130°C or lower, even more preferably 120°C or lower. The hydroxyl value of the polyester (A) is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more, and is preferably 70 mgKOH / g or less, more preferably 60 mgKOH / g or less, and even more preferably 40 mgKOH / g or less, from the viewpoints of rut resistance and surface appearance of the asphalt pavement. The weight average molecular weight Mw of the polyester (A) is preferably 5,000 or more, more preferably 7,000 or more, even more preferably 8,000 or more, from the viewpoint of the rut resistance and surface appearance of the asphalt pavement, and is preferably 70,000 or less, more preferably 40,000 or less, even more preferably 25,000 or less.

[0030] The softening point, hydroxyl value and weight average molecular weight Mw of the polyester (A) can be measured by the method described in the Examples. The softening point, hydroxyl value and weight average molecular weight Mw can be adjusted by the raw material monomer composition, molecular weight, catalyst amount or reaction conditions.

[0031] [Polyester (B)] The polyester (B) contains a structural unit derived from an alcohol component (b1) and a structural unit derived from a carboxylic acid component (b2), and in a total of 100 mol % of the alcohol component (b1) and the carboxylic acid component (b2), the total content of the alcohol component and the carboxylic acid component having an aliphatic saturated hydrocarbon skeleton is 20 mol % or more, and the total content of the alcohol component and the carboxylic acid component having the structure represented by the above-mentioned formula (1) is less than 5 mol %.

[0032] (Aliphatic saturated hydrocarbon skeleton) The total content of the alcohol component and carboxylic acid component having an aliphatic saturated hydrocarbon skeleton is 20 mol% or more, based on a total of 100 mol% of the alcohol component (b1) and the carboxylic acid component (b2). From the viewpoint of the rut resistance and surface appearance of the asphalt pavement, the total content is preferably 25 mol% or more, more preferably 30 mol% or more, even more preferably 40 mol% or more, and is preferably 85 mol% or less, more preferably 70 mol% or less, even more preferably 60 mol% or less. The aliphatic saturated hydrocarbon skeleton may be contained in both the alcohol component (b1) and the carboxylic acid component (b2), or in either the alcohol component (b1) or the carboxylic acid component (b2). Preferably, the alcohol component (b1) and the carboxylic acid component (b2), or only the alcohol component (b1), have an aliphatic saturated hydrocarbon skeleton. The carbon number of the aliphatic saturated hydrocarbon skeleton is preferably 5 or more and preferably 100 or less, more preferably 50 or less, even more preferably 20 or less, and even more preferably 10 or less, from the viewpoint of the rut resistance and surface appearance of the asphalt pavement.

[0033] (Structure represented by formula (1)) The total content of the alcohol component and the carboxylic acid component having the structure represented by formula (1) is less than 5 mol% out of 100 mol% of the total of the alcohol component (b1) and the carboxylic acid component (b2). From the viewpoint of the rut resistance and surface aesthetics of the asphalt pavement, the total content is preferably less than 1 mol%, more preferably less than 0.1 mol%, and even more preferably is substantially free of the structure represented by formula (1). [ka]

[0034] In a preferred embodiment of the polyester (B), the total content of the alcohol component having an aromatic ring skeleton and the carboxylic acid component is preferably 15 mol % or more, more preferably 20 mol % or more, even more preferably 40 mol % or more, and is preferably 70 mol % or less, more preferably 60 mol % or less, even more preferably 55 mol % or less, based on a total of 100 mol % of the alcohol component (b1) and the carboxylic acid component (b2). The aromatic ring skeleton can be derived from both the alcohol component (b1) and the carboxylic acid component (b2), or from either the alcohol component (b1) or the carboxylic acid component (b2), and is preferably derived from the carboxylic acid component (b2). The aromatic ring skeleton is derived from, for example, the above-mentioned aromatic diol or aromatic dicarboxylic acid, preferably from an aromatic dicarboxylic acid, more preferably from terephthalic acid or isophthalic acid.

[0035] In a preferred embodiment of the polyester (B), the total content of the alcohol component and the carboxylic acid component having an aliphatic saturated hydrocarbon skeleton having 5 to 100 carbon atoms is 30 mol% to 85 mol% in the total 100 mol% of the alcohol component (b1) and the carboxylic acid component (b2). From the viewpoint of the rutting resistance and surface aesthetics of the asphalt pavement, it is preferably 40 mol% or more, more preferably 45 mol% or more, even more preferably 50 mol% or more, and preferably 82 mol% or less, more preferably 80 mol% or less, even more preferably 78 mol% or less, and the total content of the alcohol component and the carboxylic acid component having an aromatic ring skeleton is 15 mol% or more, and from the viewpoint of the rutting resistance and surface aesthetics of the asphalt pavement, it is preferably 20 mol% or more, more preferably 40 mol% or more, even more preferably 45 mol% or more, and preferably 70 mol% or less, more preferably 60 mol% or less, even more preferably 55 mol% or less.

[0036] (Alcohol component (b1)) The alcohol component (b1) may be a diol, a trihydric or higher polyhydric alcohol, etc. The diol may be an aliphatic diol or an aromatic diol. These alcohol components may be used alone or in combination of two or more. From the viewpoint of the rutting resistance and surface appearance of the asphalt pavement, the aliphatic diol is preferably a saturated aliphatic diol, more preferably an α,ω-straight-chain saturated aliphatic diol. The aliphatic diol has preferably 2 or more, more preferably 3 or more, and even more preferably 5 or more carbon atoms, and preferably 100 or less, more preferably 50 or less, more preferably 20 or less, and even more preferably 10 or less.

[0037] Examples of the saturated aliphatic diol include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,16-hexadecanediol, 1,18-octadecanediol, 1,20-eicosanediol, and other saturated aliphatic diols having 100 or less carbon atoms. Among these, ethylene glycol, 1,5-pentanediol, 1,6-hexanediol, and 1,9-nonanediol are preferred. These saturated aliphatic diols can be used alone or in combination of two or more. From the viewpoint of rut resistance and surface appearance of the asphalt pavement, the content of the saturated aliphatic diol is preferably 20 mol% or more, more preferably 40 mol% or more, even more preferably 50 mol% or more, and is preferably 100 mol% or less, based on 100 mol% of the alcohol component (b1). The alcohol component (b1) may contain other alcohol components different from the saturated aliphatic diol. Examples of other alcohol components include aromatic diols such as alkylene oxide adducts of bisphenol A; trihydric or higher alcohols such as glycerin, pentaerythritol, and trimethylolpropane. These alcohol components may be used alone or in combination of two or more.

[0038] In a preferred embodiment of the alcohol component (b1), the content of saturated aliphatic diol having 5 to 100 carbon atoms is preferably 60 mol % or more, more preferably 70 mol % or more, based on 100 mol % of the alcohol component (b1).

[0039] (Carboxylic acid component (b2)) Examples of the carboxylic acid component (b2) include aliphatic monocarboxylic acids, aliphatic dicarboxylic acids, aromatic dicarboxylic acids, and polyvalent carboxylic acid compounds having a valence of 3 to 6. From the viewpoint of the rutting resistance and surface appearance of the asphalt pavement, the carboxylic acid component is preferably an aliphatic dicarboxylic acid or an aromatic dicarboxylic acid, more preferably an aromatic dicarboxylic acid. These carboxylic acid components can be used alone or in combination of two or more kinds. From the viewpoint of rut resistance and surface appearance of the asphalt pavement, the number of carbon atoms in the main chain of the aliphatic dicarboxylic acid is preferably 4 or more, more preferably 5 or more, even more preferably 6 or more, and is preferably 20 or less, more preferably 18 or less, even more preferably 16 or less. Examples of the aliphatic dicarboxylic acid include fumaric acid, sebacic acid, dodecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid, and eicosane diacid. Among these, sebacic acid is preferred. These aliphatic dicarboxylic acids can be used alone or in combination of two or more. From the viewpoint of rutting resistance and surface appearance of the asphalt pavement, the number of carbon atoms of the aromatic dicarboxylic acid is preferably 8 or more and preferably 20 or less, more preferably 16 or less, and even more preferably 12 or less. Examples of aromatic dicarboxylic acids include isophthalic acid, terephthalic acid, naphthalenedicarboxylic acid, anthracene dicarboxylic acid, and phenanthrene dicarboxylic acid. Among these, terephthalic acid is preferred. These aromatic dicarboxylic acids can be used alone or in combination of two or more. From the viewpoint of the rut resistance and surface appearance of the asphalt pavement, the content of the aliphatic dicarboxylic acid or aromatic dicarboxylic acid in the carboxylic acid component (b2) is preferably 80 mol % or more, more preferably 85 mol % or more, even more preferably 90 mol % or more, and even more preferably 95 mol % or more, and is 100 mol % or less. The carboxylic acid component (b2) may contain other carboxylic acid components different from aliphatic dicarboxylic acids and aromatic dicarboxylic acids. Examples of other carboxylic acid components include aliphatic monocarboxylic acids such as stearic acid, capric acid, lauric acid, myristic acid, palmitic acid, arachidic acid, behenic acid, and lignoceric acid; and polyvalent carboxylic acids having three or more valences such as trimellitic acid and pyromellitic acid. These carboxylic acid components may be used alone or in combination of two or more kinds.

[0040] In a preferred embodiment of the carboxylic acid component (b2), the total content of one or more acids selected from terephthalic acid and isophthalic acid in the carboxylic acid component (b2) is preferably 30 mol % or more, more preferably 40 mol % or more.

[0041] (Molar ratio of carboxylic acid component (b2) to alcohol component (b1)) The molar ratio of the carboxylic acid component (b2) to the alcohol component (b1) [carboxylic acid component (b2) / alcohol component (b1)] is preferably 0.6 or more, more preferably 0.7 or more, even more preferably 0.8 or more, from the viewpoint of adjusting the acid value and from the viewpoint of the rutting resistance and surface appearance of the asphalt pavement, and is preferably 1.5 or less, more preferably 1.3 or less, even more preferably 1.1 or less.

[0042] (Physical properties of polyester (B)) From the viewpoint of rut resistance and surface appearance of the asphalt pavement, the hydroxyl value of the polyester (B) is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more, even more preferably 15 mgKOH / g or more, and is preferably 70 mgKOH / g or less, more preferably 60 mgKOH / g or less, even more preferably 40 mgKOH / g or less. The weight average molecular weight Mw of the polyester (B) is preferably 3,000 or more, more preferably 5,000 or more, even more preferably 7,000 or more, from the viewpoint of the rut resistance and surface appearance of the asphalt pavement, and is preferably 50,000 or less, more preferably 30,000 or less, even more preferably 20,000 or less.

[0043] The hydroxyl value and weight average molecular weight Mw of the polyester (B) can be measured by the method described in the Examples. The hydroxyl value and weight average molecular weight Mw can be adjusted by the raw material monomer composition, molecular weight, catalyst amount, or reaction conditions.

[0044] The polyester (A) and the polyester (B) may be modified to such an extent that their properties are not substantially impaired. Specific examples of modified polyesters include polyesters grafted or blocked with phenol, urethane, epoxy, or the like by the methods described in JP-A-11-133668, JP-A-10-239903, JP-A-8-20636, etc. Preferred modified polyesters include urethane-modified polyesters obtained by urethane-extending polyesters with a polyisocyanate compound.

[0045] From the viewpoint of rutting resistance of asphalt pavement, the content of polyester (A) in the asphalt modifier for straight asphalt is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 80% by mass or more, and is preferably 95% by mass or less, more preferably 90% by mass or less. From the viewpoint of rutting resistance of the asphalt pavement, the content of the polyester (B) in the asphalt modifier is preferably 5 mass% or more, more preferably 10 mass% or more, and preferably 50 mass% or less, more preferably 40 mass% or less, and even more preferably 20 mass% or less.

[0046] From the viewpoint of the rut resistance and surface appearance of the asphalt pavement, the content ratio of polyester (A) and polyester (B) in the asphalt modifier for straight asphalt is, in mass ratio, polyester (A) / polyester (B) of preferably 60 / 40 or more, more preferably 65 / 45 or more, even more preferably 70 / 30 or more, even more preferably 75 / 25 or more, even more preferably 80 / 20 or more, and is preferably 99 / 1 or less, more preferably 98 / 2 or less, even more preferably 97 / 3 or less, even more preferably 95 / 5 or less, even more preferably 90 / 10 or less, and even more preferably 80 / 20 or less. That is, polyester (A) is a polyester base, and polyester (B) is a polyester auxiliary.

[0047] (Production method of polyester) The method for producing the polyester (A) and polyester (B) constituting the asphalt modifier for straight asphalt of the present invention is not particularly limited. For example, they can be produced by polycondensing the above-mentioned alcohol component (a1) and carboxylic acid component (a2), and the above-mentioned alcohol component (b1) and carboxylic acid component (b2). The temperature of the polycondensation reaction is not particularly limited, but is preferably 160° C. or higher and 260° C. or lower from the viewpoints of adjusting the reactivity and improving the rutting resistance and surface appearance of the asphalt pavement.

[0048] When the polyester used in the present invention contains constitutional units derived from ethylene glycol derived from polyethylene terephthalate and constitutional units derived from terephthalic acid derived from polyethylene terephthalate, the amount of polyethylene terephthalate present in the raw material is preferably 5 to 80 mass%, more preferably 15 to 70 mass%, and even more preferably 25 to 60 mass%, of the total amount of polyethylene terephthalate, the alcohol component, and the carboxylic acid component. By adding polyethylene terephthalate during the polycondensation reaction between the alcohol component and the carboxylic acid component, an ester exchange reaction occurs, and a polyester can be obtained in which the structural units of polyethylene terephthalate are incorporated into structural units derived from the alcohol component and structural units derived from the carboxylic acid component. Polyethylene terephthalate may be present from the start of the polycondensation reaction, or may be added to the reaction system during the polycondensation reaction. From the viewpoint of the rutting resistance and surface aesthetics of the asphalt pavement, the timing of adding polyethylene terephthalate is preferably when the reaction rate between the alcohol component and the carboxylic acid component is 10% or less, more preferably 5% or less. The reaction rate refers to the value of the amount of water produced by reaction (mol) / theoretical amount of water produced (mol)×100.

[0049] In the polycondensation reaction, a tin(II) compound not having a Sn-C bond, such as tin(II) di(2-ethylhexanoate), may be used as an esterification catalyst, and from the viewpoint of reaction rate, the amount of the tin(II) compound used may be preferably 0.01 part by mass or more, more preferably 0.1 part by mass or more, even more preferably 0.2 part by mass or more, and preferably 1.5 parts by mass or less, more preferably 0.6 parts by mass or less, per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. In the polycondensation reaction, in addition to the esterification catalyst, from the viewpoint of reaction rate, a pyrogallol compound such as gallic acid may be used as a co-catalyst, preferably at least 0.001 part by mass, more preferably at least 0.005 part by mass, even more preferably at least 0.01 part by mass, and preferably at most 0.15 part by mass, more preferably at most 0.10 part by mass, and even more preferably at most 0.05 part by mass, per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. In addition to the catalyst, from the viewpoint of reaction rate, a polymerization inhibitor such as tertiary butyl catechol may be used in the polycondensation reaction in an amount of preferably 0.001 part by mass or more, more preferably 0.01 part by mass or more, and preferably 0.5 part by mass or less, more preferably 0.2 part by mass or less, per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component.

[0050] The asphalt modifier for straight asphalt of the present invention can be mixed with straight asphalt to obtain an asphalt composition. Heated aggregate is added to the obtained asphalt composition to prepare an asphalt mixture, which can then be used for paving. The asphalt modifier for straight asphalt of the present invention can be suitably used as an asphalt modifier to be blended into an asphalt mixture containing straight asphalt and aggregate.

[0051] [Asphalt mixture] The asphalt mixture of the present invention contains straight asphalt, aggregate, polyester (A) and polyester (B). The asphalt mixture of the present invention is also prepared by blending straight asphalt, aggregate, polyester (A) and polyester (B). The asphalt mixture of the present invention is suitable for paving, and is particularly suitable for road paving. <Straight asphalt> The asphalt mixture of the present invention contains straight asphalt, which is a petroleum asphalt for paving. Straight asphalt is a residual bituminous material obtained by subjecting crude oil to atmospheric distillation or vacuum distillation.

[0052] <Aggregate> The aggregate can be selected from crushed stone, boulders, gravel, sand, recycled aggregate, ceramics, etc. In addition, the aggregate can be either coarse aggregate with a particle size of 2.36 mm or more, or fine aggregate with a particle size of less than 2.36 mm. Examples of coarse aggregate include crushed stone with a particle size range of 2.36 mm or more and less than 4.75 mm, crushed stone with a particle size range of 4.75 mm or more and less than 12.5 mm, crushed stone with a particle size range of 12.5 mm or more and less than 19 mm, and crushed stone with a particle size range of 19 mm or more and less than 31.5 mm. The fine aggregate is preferably one having a particle size of 0.075 mm or more and less than 2.36 mm. Examples of fine aggregate include river sand, dune sand, mountain sand, sea sand, crushed sand, fine sand, screenings, crushed stone dust, silica sand, artificial sand, glass cullet, foundry sand, and recycled crushed aggregate sand. The above particle size is the value specified in JIS A5001:2008. Among these, a combination of coarse aggregate and fine aggregate is preferable.

[0053] The fine aggregate may contain a filler having a particle size of less than 0.075 mm. Examples of the filler include sand, fly ash, calcium carbonate such as limestone powder, slaked lime, etc. Among these, calcium carbonate is preferred from the viewpoint of improving the strength of the asphalt pavement. From the viewpoint of improving dry strength, the average particle size of the filler is preferably 0.001 mm or more, and preferably 0.06 mm or less, more preferably 0.04 mm or less, and further preferably 0.03 mm or less. The average particle size of the filler can be measured by a laser diffraction particle size distribution measuring device. Here, the average particle size means the average particle size at 50% cumulative volume.

[0054] From the viewpoint of the rutting resistance of the asphalt pavement, the mass ratio of coarse aggregate to fine aggregate is preferably 10 / 90 or more, more preferably 20 / 80 or more, even more preferably 30 / 70 or more, and is preferably 90 / 10 or less, more preferably 80 / 20 or less, even more preferably 70 / 30 or less.

[0055] Suitable examples of blending the asphalt mixture include the following (1) to (3). (1) For example, fine-grained asphalt containing 30% by volume or more and less than 45% by volume of coarse aggregate, 30% by volume or more and less than 50% by volume of fine aggregate, and 5% by volume or more and less than 10% by volume of an asphalt composition. (2) For example, a dense-graded asphalt containing 45% by volume or more but less than 70% by volume of coarse aggregate, 20% by volume or more but less than 45% by volume of fine aggregate, and 3% by volume or more but less than 10% by volume of an asphalt composition. (3) For example, a porous asphalt containing 70% by volume or more and 80% by volume or less of coarse aggregate, 10% by volume or more and 20% by volume or less of fine aggregate, and 3% by volume or more and 10% by volume or less of an asphalt composition.

[0056] The porous asphalt can be suitably used for drainage pavement.

[0057] From the viewpoints of rut resistance and surface appearance, the aggregate content in the asphalt mixture is preferably 50% by mass or more, more preferably 75% by mass or more, even more preferably 80% by mass or more, and preferably 99% by mass or less, more preferably 98% by mass or less, even more preferably 96% by mass or less.

[0058] The mixing ratio of asphalt in conventional asphalt mixtures containing aggregate and asphalt is usually determined according to the optimal amount of asphalt obtained from the "Mix Design of Asphalt Composition" described in the "Guidelines for Pavement Design and Construction" issued by the Japan Road Association, a public interest incorporated association. In the present invention, the above-mentioned optimum amount of asphalt corresponds to the total amount of asphalt, polyester (A) and polyester (B). However, it is not necessary to be limited to the method described in the "Guidelines for Pavement Design and Construction" and it may be determined by other methods.

[0059] From the viewpoint of the rutting resistance of the asphalt pavement, the asphalt content in the asphalt mixture is preferably 1 mass% or more, more preferably 3 mass% or more, even more preferably 4 mass% or more, and preferably 20 mass% or less, more preferably 15 mass% or less, even more preferably 10 mass% or less.

[0060] (Polyester content) The total content of polyester (A) and polyester (B) in the asphalt mixture of the present invention is preferably 1 part by mass or more, more preferably 5 parts by mass or more, and even more preferably 10 parts by mass or more, per 100 parts by mass of asphalt, from the viewpoint of rut resistance and surface appearance of the asphalt pavement, and from the viewpoint of workability, it is preferably 40 parts by mass or less, more preferably 35 parts by mass or less, and more preferably 30 parts by mass or less. From the viewpoint of the rut resistance and surface appearance of the asphalt pavement, the content ratio of polyester (A) and polyester (B) in the asphalt mixture is, in mass ratio, polyester (A) / polyester (B) of preferably 60 / 40 or more, more preferably 65 / 45 or more, even more preferably 70 / 30 or more, even more preferably 75 / 25 or more, even more preferably 80 / 20 or more, and is preferably 99 / 1 or less, more preferably 98 / 2 or less, even more preferably 97 / 3 or less, even more preferably 95 / 5 or less, even more preferably 90 / 10 or less, and even more preferably 80 / 20 or less.

[0061] The asphalt mixture may further contain other components as necessary.

[0062] [Asphalt mixture manufacturing method] The asphalt mixture of the present invention can be obtained by blending asphalt, heated aggregate, polyester (A), and polyester (B). The method for producing an asphalt mixture of the present invention includes a step of mixing asphalt, heated aggregate, polyester (A), and polyester (B) simultaneously or in any order. Specific methods for producing asphalt mixtures include conventional methods for producing asphalt mixtures called the plant mix method, the premix method, etc. In both methods, asphalt and polyester are added to heated aggregate. The above mixing step is preferably any one of the following steps (i) to (iii). (i) adding and mixing asphalt to the heated aggregate, and then adding and mixing polyester (A) and polyester (B); (ii) adding and mixing the asphalt, polyester (A) and polyester (B) simultaneously to the heated aggregate; or (iii) Add and mix the pre-heated mixture of asphalt, polyester (A) and polyester (B) to the heated aggregate.

[0063] The polyester (A) and the polyester (B) may be added simultaneously or separately in a chronological order. When the polyester (A) and the polyester (B) are added separately in a chronological order, the polyester (B) may be added after the polyester (A), or the polyester (A) may be added after the polyester (B).

[0064] The temperature of the heated aggregate in methods (i) to (iii) is preferably 130°C or higher, more preferably 150°C or higher, and even more preferably 170°C or higher, from the viewpoint of the rut resistance of the asphalt pavement, and is preferably 230°C or lower, more preferably 210°C or lower, and even more preferably 200°C or lower, from the viewpoint of preventing thermal deterioration of the asphalt.

[0065] From the viewpoint of the rutting resistance of the asphalt pavement, the mixing temperature of the aggregate with the asphalt and / or polyester is preferably 130°C or higher, more preferably 150°C or higher, and even more preferably 170°C or higher, and from the viewpoint of preventing thermal deterioration of the asphalt, the mixing temperature is preferably 230°C or lower, more preferably 210°C or lower, and even more preferably 200°C or lower. The mixing time of the aggregate with the asphalt and / or polyester is not particularly limited, but is preferably 30 seconds or more, more preferably 1 minute or more, and even more preferably 2 minutes or more. The upper limit of the mixing time is not particularly limited, but is preferably about 30 minutes.

[0066] From the viewpoint of the rutting resistance of the asphalt pavement, the method for producing an asphalt mixture preferably includes a step of holding the resulting mixture at the above-mentioned mixing temperature after the mixing step. In the step of maintaining the asphalt mixture, the mixture may be further mixed. The retention time is preferably 0.2 hours or more, more preferably 0.3 hours or more, and even more preferably 0.5 hours or more. The upper limit of the time is not particularly limited, but is, for example, about 5 hours.

[0067] [Road paving method] The asphalt mixture of the present invention is suitable for road paving and is used for road paving. The road paving method includes a step of applying the asphalt mixture to a road to form an asphalt pavement layer. Specifically, the road paving method includes a step (step 1) of obtaining an asphalt mixture by mixing asphalt, the polyester (A) and the polyester (B), and aggregate, and a step (step 2) of applying the asphalt mixture obtained in step 1 to a road to form an asphalt pavement layer. The asphalt pavement layer is usually a base layer or a surface layer, and is preferably a surface layer from the viewpoint of exerting the effects of rut resistance and surface aesthetics.

[0068] From the viewpoint of rutting resistance and surface aesthetics, the thickness of the asphalt pavement layer is preferably 3 cm or more, more preferably 4 cm or more, even more preferably 4.5 cm or more, and preferably 7 cm or less, more preferably 6 cm or less, even more preferably 5.5 cm or less. In another embodiment of the present invention, the asphalt pavement layer can be a thin layer pavement, and the thickness of the surface layer is preferably 1 cm or more, more preferably 1.5 cm or more, even more preferably 2 cm or more, and preferably 4 cm or less, more preferably 3.5 cm or less, even more preferably 3 cm or less. The asphalt mixture may be compacted and applied in a similar manner using a known construction machine. The compaction temperature when used as a heated asphalt mixture is preferably 100°C or higher, more preferably 120°C or higher, and even more preferably 130°C or higher, from the viewpoint of the rutting resistance of the asphalt pavement, and is preferably 200°C or lower, and more preferably 180°C or lower. EXAMPLES

[0069] Various physical properties were measured and evaluated by the following methods. In the following examples and comparative examples, parts and percentages are by weight unless otherwise specified.

[0070] (1) Hydroxyl value of polyester The hydroxyl value of the polyester was measured according to the method of JIS K0070: 1992. However, the measurement solvent was changed from the mixed solvent of ethanol and ether specified in JIS K0070: 1992 to a mixed solvent of acetone and toluene (acetone:toluene = 1:1 (volume ratio)).

[0071] (2) Softening point of polyester Using a flow tester "CFT-500D" (Shimadzu Corporation), 1 g of the sample was heated at a temperature increase rate of 6°C / min, while applying a load of 1.96 MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1 mm and a length of 1 mm. The plunger descent amount of the flow tester was plotted against the temperature, and the temperature at which half of the sample flowed out was taken as the softening point.

[0072] (3) Weight average molecular weight (Mw) of polyester The weight average molecular weight was determined by gel permeation chromatography (GPC) according to the following method. (i) Preparation of sample solution The sample was dissolved in chloroform at 40° C. to a concentration of 0.5 g / 100 mL. Next, this solution was filtered using a PTFE-type membrane filter “DISMIC-25JP” (manufactured by Toyo Roshi Kaisha, Ltd.) with a pore size of 0.20 μm to remove insoluble components, thereby obtaining a sample solution. (ii) Molecular weight measurement The following measuring device and analytical column were used, and chloroform was used as the eluent at a flow rate of 1 mL per minute. The column was stabilized in a thermostatic chamber at 40°C. 200 μL of the sample solution was injected into the column and the measurement was performed. The molecular weight of the sample was calculated based on a calibration curve that had been prepared in advance. The calibration curve used here included several types of monodisperse polystyrene (A-500 (5.0 × 10 2 ), A-1000(1.01×10 3 ), A-2500(2.63×10 3 ), A-5000(5.97×10 3 ), F-1(1.02×10 4 ), F-2(1.81×10 4 ), F-4(3.97×10 4 ), F-10(9.64×10 4 ), F-20(1.90×10 5 ), F-40(4.27×10 5 ), F-80(7.06×10 5 ), F-128(1.09×10 6 )) was used as a standard sample. The numbers in parentheses indicate the molecular weight. Measuring device: "HLC-8320GPC" (Tosoh Corporation) Analytical column: "TSKgel Super HZM" + "TSKgel Super H-RC" x 2 (manufactured by Tosoh Corporation)

[0073] Production Example 1 (Polyester A-1) The polyester alcohol components and terephthalic acid shown in Table 1 were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and the amounts of tin(II) di(2-ethylhexanoate) and gallic acid shown in Table 1 were added in a nitrogen atmosphere. The mixture was heated to 235° C. over 3 hours in a mantle heater, held for 5 hours after reaching 235° C., and then cooled to 180° C. After cooling to 180° C., alkenyl succinic anhydride was added, the mixture was heated to 210° C. over 2 hours, held at 210° C. for 1 hour, and reacted under reduced pressure at 8.3 kPa until the softening point shown in Table 1 was reached, yielding the target polyester A-1. The alkenyl succinic anhydride used had an average number of moles added of 12 and a molecular weight of 256 (calculated from GC-MS and saponification value).

[0074] Production Example 2 (Polyester B-1) The polyester alcohol components and terephthalic acid shown in Table 1 were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and the amounts of tin(II) di(2-ethylhexanoate) and gallic acid shown in Table 1 were added in a nitrogen atmosphere, and the temperature was raised to 235°C over 3 hours in a mantle heater, and after reaching 235°C, the reaction was maintained for 5 hours. After visually confirming that the PET particles had disappeared from the reaction product, the reaction was cooled to 180°C. Next, adipic acid was added, and the temperature was raised from 180°C to 210°C over 3 hours. After reaching 210°C, the reaction was continued at 10 kPa until the softening point shown in Table 1 was reached, and polyester B-1 was obtained.

[0075] Production Example 3 (Polyester C-1) The target polyester C-1 was obtained in the same manner as in Production Example 1, except that the raw material monomer composition was changed to that shown in Table 1 and gallic acid was not added.

[0076] Production Examples 4 and 5 (Polyesters D-1 and E-1) The polyester alcohol components and terephthalic acid shown in Table 1 were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and the amount of di(2-ethylhexanoate)tin(II) shown in Table 1 was added in a nitrogen atmosphere, and the temperature was raised to 235°C over 3 hours in a mantle heater, and after reaching 235°C, it was held for 5 hours. After visually confirming that the PET particles had disappeared from the reaction product, it was cooled to 180°C. After cooling to 180°C, alkenyl succinic anhydride was added, the temperature was raised to 210°C over 2 hours, and the reaction was held at 210°C for 1 hour. After the reaction was carried out under reduced pressure at 8.3 kPa, the reaction was continued until the softening point shown in Table 1 was reached, and the target polyesters D-1 and E-1 were obtained.

[0077] Manufacturing Example 6 (Polyester F-1) The polyester alcohol component and terephthalic acid shown in Table 1 were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and the amounts of di(2-ethylhexanoate)tin(II) and gallic acid shown in Table 1 were added in a nitrogen atmosphere, and the temperature was raised to 235°C over 3 hours in a mantle heater, and after reaching 235°C, the reaction was maintained for 5 hours. After visually confirming that the PET particles had disappeared from the reaction product, the reaction was cooled to 180°C. Next, adipic acid was added, and the temperature was raised from 180°C to 210°C over 3 hours. After reaching 210°C, the reaction was continued at 10 kPa until the softening point shown in Table 1 was reached, and polyester resin F-1 was obtained.

[0078] [Table 1]

[0079] Production Examples 7, 9 and 10 (Polyesters A-2, C-2 and D-2) The raw material monomers shown in Table 2 were placed in a 10 L four-neck flask equipped with a thermometer, a stainless steel stirring rod, a dehydration tube, a nitrogen inlet tube, and a thermocouple, and the amounts of tin(II) di(2-ethylhexanoate) and gallic acid shown in Table 2 were added in a nitrogen atmosphere. The mixture was kept at 180°C for 2 hours and then heated to 210°C over 3 hours. The mixture was then reacted at 210°C for 4 hours and then at 8.3 kPa for 1 hour to obtain polyesters A-2, C-2, and D-2.

[0080] Production Example 8 (Polyester B-2) The raw material monomers shown in Table 2 were placed in a 10 L four-neck flask equipped with a thermometer, a stainless steel stirring rod, a dehydration tube, a nitrogen inlet tube, and a thermocouple, and in a nitrogen atmosphere, tin(II) di(2-ethylhexanoate) and gallic acid in the amounts shown in Table 2 were added, and the mixture was maintained at 180° C. for 2 hours under a nitrogen atmosphere, and then heated to 210° C. over 3 hours, and reacted at 210° C. for 4 hours. Thereafter, the mixture was cooled to 150° C., and sebacic acid was added, and the mixture was heated to 200° C. over 5 hours, and then reacted at 8.3 kPa for 1 hour to obtain polyester B-2.

[0081] Manufacturing Example 11 (Polyester E-2) The raw material monomers other than stearic acid shown in Table 2 were placed in a 10 L four-neck flask equipped with a thermometer, a stainless steel stirring rod, a dehydration tube, a nitrogen inlet tube, and a thermocouple, and in a nitrogen atmosphere, tin(II) di(2-ethylhexanoate) and gallic acid in the amounts shown in Table 2 were added, the mixture was kept at 140° C. for 6 hours, and then heated to 200° C. over 6 hours, reacted at 200° C. for 1 hour, and then cooled to 180° C. Next, stearic acid was added, and the mixture was heated from 180° C. to 210° C. over 3 hours. After reaching 210° C., the mixture was reacted at 8.3 kPa for 1 hour to obtain polyester E-2.

[0082] [Table 2]

[0083] The abbreviations for the alcohol components and carboxylic acid components used are as follows: EG: Ethylene glycol 1,5-PD: 1,5-pentanediol 1,6-HD: 1,6-hexanediol 1,9-ND: 1,9-nonanediol BPA-EO: Polyoxyethylene (2.2 moles) adduct of bisphenol A BPA-PO: Polyoxypropylene (2.2 moles) adduct of bisphenol A SA: Sebacic acid TPA: terephthalic acid ADA: Adipic acid ASAN: alkenyl succinic anhydride (a mixture of succinic acids with alkenyl groups, the average number of carbon atoms in the alkenyl group is 12)

[0084] Example 1 As a binder mixture, 1,000 g of straight asphalt (Idemitsu Kosan Co., Ltd., 60-80 grade) heated to 180°C was placed in a 3 L stainless steel container and stirred at 100 rpm. Next, 170 g of polyester A-1 (17 parts by mass per 100 parts by mass of asphalt) was gradually added, and immediately thereafter, 30 g of polyester A-2 (3 parts by mass per 100 parts by mass of asphalt) was gradually added. The mixture was stirred at 300 rpm for 2 hours to prepare an asphalt composition (AS-1).

[0085] Next, 15 kg of aggregate heated to 180° C. (see below for the composition of the aggregate) was placed in an asphalt mixer and mixed for 60 seconds at 180° C. Next, 986 g of the asphalt composition (AS-1) was added, and mixed for 2 minutes in the asphalt mixer. The resulting asphalt mixture was quickly filled into a 300 x 300 x 50 mm formwork. Using a roller compactor (manufactured by Iwata Kogyosho Co., Ltd.), the mixture was subjected to 25 rotations of pressure treatment at a temperature of 150°C and a load of 0.44 kPa to prepare an asphalt specimen (M-1a) without heat curing. Separately, an asphalt specimen (M-1b) was prepared under normal curing conditions following the same procedure as described above, except that the asphalt mixture was stored at 180°C for 2 hours before being filled into the formwork.

[0086] <Aggregate composition> No. 6 crushed stone 50.9 parts by weight Crushed sand 1 10.4 parts by mass Crushed sand 2 22.1 parts by mass Fine sand 10.4 parts by mass Stone powder (calcium carbonate) 6.2 parts by weight Passed mass%: Sieve size 15 mm: 100% by mass Sieve size 10 mm: 85.6% by mass Sieve size 5 mm: 49.7% by mass Sieve size 2.5 mm: 44.6% by mass Sieve size 1.2 mm: 31.6% by mass Sieve size 0.6 mm: 21.3% by mass Sieve size 0.3 mm: 12.7% by mass Sieve size 0.15mm: 7.1% by mass

[0087] [evaluation] The above-mentioned asphalt specimen (M-1a) and asphalt specimen (M-1b) were subjected to the following evaluation tests. The effects of heat curing were evaluated by comparing the evaluation results of asphalt specimen (M-1a) and asphalt specimen (M-1b). <Amount of rutting> The asphalt specimen was immersed in hot water set at 60°C in a 60°C thermostatic chamber, and a wheel tracking tester (manufactured by Iwata Kogyosho Co., Ltd., load 1,370N, iron wheel width 47mm, linear pressure 291.5N / cm) was used to move the wheel back and forth over the specimen at a speed of 15 times / min, and the amount of displacement after 2,500 passes was measured. Other measurement conditions were in accordance with the "B003 Wheel Tracking Test" described in the "Pavement Survey and Testing Method Handbook" published by the Japan Road Association. The results are shown in Table 3.

[0088] <Filling level> (Filling degree) The filling degree of the asphalt specimen was calculated according to the following formula. The results are shown in Table 3. Filling degree = (void ratio when polyester is not added) / (void ratio when polyester is added) (porosity) The void ratio used to calculate the packing degree was calculated according to the following formula. Porosity = 100 x {1-(specimen bulk density) / (theoretical density)} (Each physical property value) Each physical property used to calculate the porosity was calculated according to the following formula. Bulk density of specimen = (mass in air) / (surface dry mass - mass in water) Theoretical density = 1 / [{(1-asphalt addition rate) / 100 / aggregate specific gravity (surface dry)}+(asphalt addition rate) / 100 / 1.04] The surface dry weight is the mass of the test specimen after it has been immersed in water for 3 minutes and then the surface has been wiped. The aggregate specific gravity (surface dry) is the specific gravity taking into account asphalt absorption, and was set to a constant of 2.618. The results are shown in Table 3.

[0089] Examples 2 to 10, Comparative Examples 1 to 3 Asphalt specimens were prepared in the same manner as in Example 1, except that the blend ratio was changed to that shown in Table 3. 945 g of the asphalt composition was used in Example 2, 822 g in Comparative Example 1, and 986 g in the other cases. An evaluation test of the strength development was performed, and the results are shown in Table 3.

[0090] [Table 3]

[0091] From the results in Table 3, it can be seen that the asphalt mixture of the present invention containing a combination of a specified polyester (A) and a specified polyester (B) has a small amount of rutting in asphalt specimens produced under normal curing conditions, exhibits excellent adhesive strength, and is excellent in rutting resistance. In particular, when a specific polyester (B) is contained, even asphalt specimens produced under conditions without heat curing have excellent rutting resistance. In addition, the asphalt mixture of the present invention containing a combination of a specified polyester (A) and a specified polyester (B) can be made to have a high filling degree, as can be seen from the results in Table 3. Furthermore, the results in Table 3 show that a high filling degree results in excellent rutting resistance. In addition, because the asphalt mixture of the present invention has a high filling rate, slight deviations in surface flatness and microcracks can be suppressed, resulting in excellent surface aesthetics. It is expected that the asphalt mixture will form a pavement surface with excellent rut resistance in specially formulated asphalt pavements such as drainage pavements and thin-layer pavements.

Claims

1. An asphalt modifier for straight asphalt comprising a polyester (A) and a polyester (B), The polyester (A) contains a structural unit derived from an alcohol component (a1) and a structural unit derived from a carboxylic acid component (a2), and the total content of the alcohol component and the carboxylic acid component having a structure represented by the following formula (1) is 10 mol % or more and 70 mol % or less relative to 100 mol % in total of the alcohol component (a1) and the carboxylic acid component (a2): The polyester (B) contains a structural unit derived from an alcohol component (b1) and a structural unit derived from a carboxylic acid component (b2), and, in a total of 100 mol % of the alcohol component (b1) and the carboxylic acid component (b2), the total content of the alcohol component and the carboxylic acid component having an aliphatic saturated hydrocarbon skeleton having from 5 to 100 carbon atoms is from 20 mol % to 85 mol %, and the total content of the alcohol component and the carboxylic acid component having a structure represented by the following formula (1) is from 0 mol % to less than 5 mol %. 【Chemistry 1】

2. The asphalt modifier for straight asphalt according to claim 1, wherein the content of the alkylene oxide adduct of bisphenol A in the alcohol component (a1) is 20 mol% or more and 100 mol% or less.

3. The asphalt modifier for straight asphalt according to claim 1 or 2, wherein the hydroxyl value of the polyester (A) is 10 mg KOH / g or more and 60 mg KOH / g or less.

4. The asphalt modifier for straight asphalt according to any one of claims 1 to 3, wherein the total content of the alcohol component and the carboxylic acid component having an aliphatic saturated hydrocarbon skeleton having 5 to 100 carbon atoms is 30 mol% to 85 mol%, and the total content of the alcohol component and the carboxylic acid component having an aromatic ring skeleton is 15 mol% to 70 mol%, out of a total of 100 mol% of the alcohol component (b1) and the carboxylic acid component (b2).

5. The asphalt modifier for straight asphalt according to any one of claims 1 to 4, wherein the content of saturated aliphatic diol having 5 to 100 carbon atoms in the alcohol component (b1) is 60 mol% or more and 100 mol% or less.

6. The asphalt modifier for straight asphalt according to any one of claims 1 to 5, wherein the content of one or more selected from terephthalic acid and isophthalic acid in the carboxylic acid component (b2) is 30 mol% or more and 100 mol% or less.

7. The asphalt modifier for straight asphalt according to any one of claims 1 to 6, wherein the hydroxyl value of the polyester (B) is 10 mg KOH / g or more and 60 mg KOH / g or less.

8. The asphalt modifier for straight asphalt according to any one of claims 1 to 7, wherein the mass ratio of the polyester (A) to the polyester (B) is 60 / 40 or more and 99 / 1 or less.

9. An asphalt mixture comprising straight asphalt, aggregate, polyester (A) and polyester (B), The polyester (A) contains a structural unit derived from an alcohol component (a1) and a structural unit derived from a carboxylic acid component (a2), and the total content of the alcohol component and the carboxylic acid component having a structure represented by the following formula (1) is 10 mol % or more and 70 mol % or less relative to 100 mol % in total of the alcohol component (a1) and the carboxylic acid component (a2): The polyester (B) contains a structural unit derived from an alcohol component (b1) and a structural unit derived from a carboxylic acid component (b2), and, in a total of 100 mol% of the alcohol component (b1) and the carboxylic acid component (b2), the total content of the alcohol component and the carboxylic acid component having an aliphatic saturated hydrocarbon skeleton having from 5 to 100 carbon atoms is from 20 mol% to 85 mol%, and the total content of the alcohol component and the carboxylic acid component having a structure represented by the following formula (1) is from 0 mol% to less than 5 mol%. 【Chemistry 2】

10. An asphalt mixture comprising straight asphalt, aggregate, polyester (A) and polyester (B), The polyester (A) contains a structural unit derived from an alcohol component (a1) and a structural unit derived from a carboxylic acid component (a2), and the total content of the alcohol component and the carboxylic acid component having a structure represented by the following formula (1) is 10 mol % or more and 70 mol % or less relative to 100 mol % in total of the alcohol component (a1) and the carboxylic acid component (a2): The polyester (B) contains a structural unit derived from an alcohol component (b1) and a structural unit derived from a carboxylic acid component (b2), and, in a total of 100 mol% of the alcohol component (b1) and the carboxylic acid component (b2), the total content of the alcohol component and the carboxylic acid component having an aliphatic saturated hydrocarbon skeleton having from 5 to 100 carbon atoms is from 20 mol% to 85 mol%, and the total content of the alcohol component and the carboxylic acid component having a structure represented by the following formula (1) is from 0 mol% to less than 5 mol%. 【Chemistry 3】

11. The asphalt mixture according to claim 9 or 10, wherein the total content of the polyester (A) and the polyester (B) is 1 part by mass or more and 40 parts by mass or less per 100 parts by mass of the straight asphalt.

12. A method for producing an asphalt mixture, comprising a step of mixing straight asphalt, heated aggregate, polyester (A) and polyester (B), The polyester (A) contains a structural unit derived from an alcohol component (a1) and a structural unit derived from a carboxylic acid component (a2), and the total content of the alcohol component and the carboxylic acid component having a structure represented by the following formula (1) is 10 mol % or more and 70 mol % or less relative to 100 mol % in total of the alcohol component (a1) and the carboxylic acid component (a2): The polyester (B) contains a structural unit derived from an alcohol component (b1) and a structural unit derived from a carboxylic acid component (b2), and, in a total of 100 mol % of the alcohol component (b1) and the carboxylic acid component (b2), the total content of the alcohol component and the carboxylic acid component having an aliphatic saturated hydrocarbon skeleton having from 5 to 100 carbon atoms is from 20 mol % to 85 mol %, and the total content of the alcohol component and the carboxylic acid component having a structure represented by the following formula (1) is from 0 mol % to less than 5 mol %. 【Chemistry 4】

13. A road paving method comprising a step of applying the asphalt mixture according to any one of claims 9 to 11 to a road to form an asphalt pavement layer.

Citation Information

Patent Citations

  • Road paving composition

    JP1989271458A

  • Asphalt composition

    JP1992008766A

  • Asphalt composition

    JP1992320453A

  • Asphalt composition

    JP2019019325A

  • Asphalt composition

    JP2020079398A